2005
DOI: 10.1086/432139
|View full text |Cite
|
Sign up to set email alerts
|

Does Serotonin Influence Aggression? Comparing Regional Activity before and during Social Interaction

Abstract: Serotonin is widely believed to exert inhibitory control over aggressive behavior and intent. In addition, a number of studies of fish, reptiles, and mammals, including the lizard Anolis carolinensis, have demonstrated that serotonergic activity is stimulated by aggressive social interaction in both dominant and subordinate males. As serotonergic activity does not appear to inhibit agonistic behavior during combative social interaction, we investigated the possibility that the negative correlation between sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 152 publications
4
97
0
2
Order By: Relevance
“…Our results support the idea that differing dynamics of the stress response may be a consistent and partly inherited trait. Other studies have indicated that this trait may be a cause, as much as a consequence, of social status (Pottinger and Pickering, 2001;Øverli et al 2004;Summers et al 2005). Salmonid fish can exhibit physiological colour change during stress; subordinate individuals e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the idea that differing dynamics of the stress response may be a consistent and partly inherited trait. Other studies have indicated that this trait may be a cause, as much as a consequence, of social status (Pottinger and Pickering, 2001;Øverli et al 2004;Summers et al 2005). Salmonid fish can exhibit physiological colour change during stress; subordinate individuals e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more likely, though, is a connection to aggression. In anole lizards, subordinate (less aggressive) males have higher baseline serotonergic activity in the AMY than their more aggressive counterparts (Summers et al, 2005). Plasma T increases with aggressive encounters in anoles (Yang and Wilczynski, 2002).…”
Section: Potential Functional Explanations Of Differential C-fos Exprmentioning
confidence: 98%
“…Increased amygdalar serotonergic activity is associated with social stress across vertebrate taxa [10], and is known to enhance mammalian hypothalamic-pituitary-adrenal (HPA) axis activity and glucocorticoid release [51,52]. The rapid increases in A. carolinensis amygdalar DA levels with social threat occurred in areas homologous with the central, lateral and medial nuclei of the mammalian amygdala [23][24][25].…”
Section: Effects Of Social Threat On Limbic Monoaminesmentioning
confidence: 99%
“…In particular, alterations to dopamine (DA) and serotonin (5-HT) function within discrete basal ganglia and mesolimbic nuclei, including key forebrain regions such as the nucleus accumbens (NAc) and amygdala, occur during or immediately following production of agonistic social behavior [4,[8][9][10]. Enhanced DA activity in the NAc normally mediates expression of motivated or goal-directed behaviors during both rewarding and aversive situations [11,12], while increased amygdalar 5-HT activity is associated with stress, fear and anxiety [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation